Superstructure optimisation of blended-biomass hybrid poly gasification and utilisation system - Ahmed AlNouss (9872265) (2023)
Renewable fuel generation and reducing reliance on fossil fuels are essential components of sustainable development. Manufacturing and use of petrochemicals are such an important economic pillar of contemporary civilisation. Therefore, there is a strong incentive to allocate alternative production pathways in order to conserve scarce resources. In order to minimise global emissions, it is also necessary to utilise environment wastes to generate value-added goods. This study demonstrates the sustainability assessment of various biomass gasification utilisation strategies developed through the poly-generation process. The superstructure network, which consists of different biomass feedstock (sources) and prospective uses (sinks) among the various gasification alternatives (pools), is examined to find the most cost-effective and ecologically beneficial production routes. Superstructure optimisation aids decisions on biomass feedstock mixing and subsequent utilisation, while taking both economic and environmental concerns into account. The results indicated the importance of biomass feedstock blending in enhancing the profitability of the process and lowering the requirement of gasifying agents. The findings indicated the domination of the power generation technique at 95.9% for oxygen gasification and methanol production for both oxygen/steam and steam-only gasification options at 92.5% when economic objective is considered. However, when the environmental objective is considered, urea generation turned to dominate the utilisation allocation at 94.9% for oxygen gasification, and methanol dominated the allocation at 92.5% for oxygen/steam and steam-only gasification options. Nevertheless, when both objectives are considered concurrently, urea dominated the strategies in all scenarios with a varying allocation of 38%–95%. The former solution maximiser the net profit at 0.124 $/kg biomass, and minimised net emissions at 0.58 kg CO2/kg biomass. Additionally, the study highlights the excellence of steam-only gasification over oxygen/steam and oxygen-only gasification options in delivering value-added products with higher profits and lower emissions.  Other Information Published in: Journal of Cleaner Production License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.jclepro.2023.137667